A fast-response electrochromic device based on a composite gel film comprising triphenylamine derivatives and WO3. (11th March 2021) - Zhang, Xuejian; Zeng, Jinming; Xu, Zipeng; Zhu, Mimi; Liu, Ping
Abstract : The WO3 /TPB-PSSO-based composite device containing TPB-PSSO and WO3 exhibits fast-response, rich color changes, and good cycling stability. Abstract : To obtain an electrochromic device with a quick response and multicolor change, N, N ′-(4-((3-(triethoxysilyl)propyl)imino)methyl)phenyl- N, N ′-diphenyl-4, 4′-biphenyl-diamine (TPB-PSSO) containing a tetraphenylbenzidine (TPB) unit and siloxane group was synthesized, and its electrochromic properties were investigated. Using the TPB-PSSO gel film and a WO3 /TPB-PSSO gel film as active materials, electrochromic devices (ECDs) having the structures indium tin oxide (ITO)/TPB-PSSO gel film/ITO and ITO/WO3 film/TPB-PSSO gel film/ITO, respectively, were prepared. These two devices exhibited a fast response according to chronoamperometry measurements, with coloring and bleaching times of 4 and 9 ms and 5 and 5 ms, respectively.